Interparental conflicts and the development of psychopathology in adolescents and young adults - Melo, Olga; Mota, Catarina Pinheiro (Paidéia (Ribeirão Preto), 2014)
The objective in this study was to analyze to what extent inter parental conflicts and divorce act as predictors of psychopathological development in young people from intact and divorced families. The participants were 827 Portuguese young people between 13 and 25 years of age. A sociodemographic questionnaire, the Children’s Perception of Interparental Conflict Scale and the Brief Symptom Inventory were used. Significant difference in the psychopathology were found with regard to gender, age and family structure. As verified, the intensity and lack of solution of the inter parental conflicts positively predict the development of psychopathology. In conclusion, the children whose parents are separated or divorced perceive the frequency and intensity of inter parental conflicts more highly, but present a higher solution level of the inter parental conflicts and higher psychopathology levels. Nevertheless, the family structure has no moderating effect on the interaction between the inter parental conflicts and the development of pyschopathology.